Pedagogical practices in vocal jazz improvisation. - Walker, Cherilee Wadsworth (My University, 2005)
There were high levels of agreement regarding which techniques were considered most and least important. However, several differences in satisfaction levels arose, suggesting that perhaps the intention and application of these teaching strategies is not fully understood. While few differences based upon gender and ethnicity were discovered, the wealth of anecdotal information implies that these issues have not yet been resolved.

Surveys were distributed to members of the International Association for Jazz Education having indicated an interest in vocal jazz. Respondents were asked to rate techniques documented in jazz literature reflecting the relative importance of each to developing skill in vocal jazz improvisation. Additionally, subjects were asked to identify persons they felt had made significant contribution to the teaching of vocal jazz, understanding that individuals receiving the most mentions would be contacted for interviews. Interviewees were first asked to describe their own teaching, then assist in interpreting the results of the survey.

Research into appropriate teaching methods has not kept pace with the growing need for understanding how vocalists learn to improvise. The purpose of this study was to poll ensemble directors and performers concerned with vocal jazz education regarding various pedagogical techniques for teaching improvisation. It was hoped this would reveal what strategies, skills, and aptitudes are most important in terms of musical development, as well as any trends related to gender, ethnicity, primary instrument, level and focus of education, and differences between directors' and performers' perspectives.
Keywords: Vocal music Instruction and study.; Improvisation (Music); Education, Music.